Identify and Analyze the Role of Human Capital with its Components in Leadership Requirements Achievement - Ismail, Jagar M.; Nouri, Rang M.; Haji, Avan Y. (Humanities Journal of University of Zakho, 2017)
The current study attempts to identify and analyze the role of human capital with its components (knowledge, skills, abilities) in leadership requirements achievement which includes creativity, risk, proactive and independence. To achieve the study objectives, (51) questionnaires have been distributed to the teaching staff of the university of Zakho randomly which comprise 72% of the staff as a whole. Descriptive and analytical statistical methods have been adopted to determine the availability of human capital dimensions and entrepreneuership requirements in the University of Zakho so as to enable the university to play a leading role among other universities. The study has come up with important results and it has depended on these results to make its recommendations and suggestions which they are seen very important the mentioned university.